2013
DOI: 10.4038/jfa.v3i1-2.5170
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency in Intercropped Pineapple Production in Kurunegala District

Abstract: The objective of the study was to estimate the current level of technical efficiency and to identify the factors affecting technical efficiency of intercropped pineapple production in Kurunegala district. A questionnaire based survey was carried out to collect the data from eighty pineapple growers. The data were analyzed by using the stochastic frontier production function approach. The pineapple production was determined as a function of land extent, plant density, labour, fertilizer, agrochemicals and worth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
3
7
0
1
Order By: Relevance
“…Results from Table 1 revealed that 88.3% of the respondents were males which implied that pineapple production in the study area was largely dominated by the males. This conforms to the findings of Fawole (2008) and Baruwa (2013) that pineapple [7] Technical Efficiency of Pineapple Production in Osun State, Nigeria production is male dominated. Majority of the farmers (75.8%) were within 41-60 years age group with mean of 54 years.…”
Section: Socio Economic Characteristics Of the Pineapple Farmerssupporting
confidence: 91%
“…Results from Table 1 revealed that 88.3% of the respondents were males which implied that pineapple production in the study area was largely dominated by the males. This conforms to the findings of Fawole (2008) and Baruwa (2013) that pineapple [7] Technical Efficiency of Pineapple Production in Osun State, Nigeria production is male dominated. Majority of the farmers (75.8%) were within 41-60 years age group with mean of 54 years.…”
Section: Socio Economic Characteristics Of the Pineapple Farmerssupporting
confidence: 91%
“…This implies that there is a scope for increasing pineapple production with expected increase of 0.28% for a 1% increase in crop area. The finding is also supported by the study of [28] where area under pineapple cultivation had positive significant effect on production. A greater investment in tillage would increase pineapple production as the coefficient is significantly positive and the average increase in production being 0.03% for a 1% increase in tillage cost.…”
Section: Empirical Results Of the Stochastic Production Frontier Modelsupporting
confidence: 59%
“…Counseling and off-farm income results positive and significant to the increasing of technical inefficiency. Farmer that only focused on the farming will be technically efficient compare than farmer that has off-farm activities [9], [15].…”
Section: The Tobit Resultsmentioning
confidence: 99%
“…Theoretically, there are three sources of productivity improvements, technological change/TC, increasing of technical efficiency/TE and economic of scale/ES [8]. Some of study results showed that production inefficiency level influenced by socio-economic and demography variables, such as farmer age, number of family member, education level, association participation, knowledge on cultivation technology, experience and off farm income [1], [4], [9].…”
Section: Introductionmentioning
confidence: 99%